Creation and Analysis of Corpus of Short Prose by Latvian Women Writers - Kārkla, Zita; Matulis, Haralds (Respectus Philologicus, 2023)
The article aims to present the creation of the text corpus of short prose by Latvian women writers and a pilot study on the distribution of body words in the corpus. The corpus development is a part of the research process, which aligns with the goals and perspectives of feminist literary history. First, the paper introduces the design of the corpus. Consisting of 259 texts, published between 1893 and 2002, it is the first literary corpus focusing on Latvian women writers and on short prose. Given that short forms have long dominated women’s prose, this focus was a conscious decision to highlight women’s contribution to writing. Further, the article presents the methods of distant reading that were applied to identify the distribution of body words in the texts. The desire to reintroduce women into the history of literature has also led to a focus on the body. While writing is mediated through the body, it is also a space to explore and take possession of the body. Finally, by combining the results of distant reading with examples of close reading, the distribution of body words in different periods is compared.